FACTORS OF LIFE QUALITY IMPROVEMENT AFTER HEART TRANSPLANTATION: PREDICTIVE SIGNIFICANCE OF CARDIOPULMONARY EXERCISE TEST - O. V. Kamenskaya; I. Yu. Loginova; D. V. Doronin; A. M. Chernyavsky; A. M. Karaskov (Российский кардиологический журнал, 2017)
Aim. Evaluation of prognostic significance of the parameters of cardiopulmonary exercise test in life quality improvement for the post-cardiac transplantation patients.Material and methods. Into the study, 40 patients included, with severe chronic heart failure (CHF), included in the waiting list for cardiac transplantation. Before and after orthotopic heart transplantation (OHT), clinical status was evaluated, cardiopulmonary exercise testing parameters (CET) and life quality by SF-36.Results. After OHT the significant life quality improvement noted, by the scale “Physical health” from 36 (32-45) points before surgery to 52 (49-55) points (p<0,05) and “Psychological health” from 38 (34-50) to 51 (50-56) points. In 13% cases life quality improvement was not noted. Among the CET parameters, significant relation with life quality improvement by “Physical” scale showed the preoperation level of exercise tolerance (ОR 2,10 (1,08-9,80), p=0,001), peak of oxygen consumption (OR 1,20 (0,97-2,61), p=0,037), efficacy of oxygen consumption in exertion (OR 0,68 (0,36-1,27), p=0,047). Also, it was shown that life quality increase after OHT depends on efficacy of oxygen consumption baseline return in first minute (OR 1,13 (1,02-1,27), p=0,024). Any relations of CET with “Psychological” life quality by SF-36 were not noted.Conclusion. Exercise tolerance, peak oxygen consumption, exertion ventilatory efficacy, efficacy of oxygen consumption baseline return after exercise, by CET in severe CHF patients, have high predictive value in evaluation of probability of life quality improvement by the scale “Physical health” of SF-36 after cardiac transplantation.